MONOPOLAR DIATHERMY AS COMPARED TO SILK LIGATURES FOR PER OPERATIVE HAEMORRHAGE CONTROL DURING TONSILLECTOMY: Pre operative Haemorrhage Control During Tonsillectomy - Ayub, Zeeshan; Ahmed, Bashir (Pakistan Armed Forces Medical Journal, 2009)
Objective: To determine whether monopolar diathermy is a better tool for haemostasis compared to tying of silk ligatures.Study Design: Quasi-experimental study.Place and Duration of Study: The study was done in ENT department of Combined Military Hospital Rawalpindi from July 2006 to March 2007.  Patients and Methods: Seventy patients were included in this study and were divided into two groups of thirty-five each; one group underwent tonsillectomy with monopolar diathermy for haemorrhage control and tying of silk ligatures for hemostasis in second group. Chi square test was used as the test of significance.Results: Monopolar diathermy is shown to be a better method of haemorrhage control as compared to tying of silk ligatures (p-value